Physical Foundations of Vickers Hardness Determination - Moshchenok, Vasyl (Харківський національний автомобільно-дорожній університет, 2026)
Physical Foundations of Vickers Hardness Determination is a scientific monograph devoted to one of the most important methods of hardness testing, combining the classical principles of testing with modern physical, metrological, and digital approaches to the analysis of results. The book consistently presents the historical development of the Vickers method, the geometric foundations of hardness calculation, the physical meaning of the classical formula, and the specific features of modern hardness testers, indenters, hardness reference blocks, and the regulatory framework for testing. Particular attention is paid to new approaches to the determination of surface, projection, and volumetric hardness, as well as to the comparison of the recovered and unrecovered indentation methods. The monograph includes experimental studies of steel, bronze, duralumin, brass, and copper, along with a description of a software-methodological complex and laboratory work performed in the Excel environment. The publication is intended for researchers, engineers, university teachers, postgraduate students, and students of technical specialties working in the fields of materials science, deformation mechanics, and hardness testing.
Keywords: Vickers hardness test; hardness testing of materials; indentation hardness; materials science and metallurgy; microhardness and macrohardness; surface projection volumetric hardness; instrumented indentation and Vickers method